Visual outcomes after cataract surgery: topical nonsteroidal anti-inflammatory drug prophylaxis compared with prednisolone. Issue 7 (July 2021) - Shorstein, Neal H.; Carolan, James; Liu, Liyan; Alexeeff, Stacey E.; Amsden, Laura B.; Herrinton, Lisa J.
Abstract : In an observational study, the authors compared NSAID and prednisolone and found no statistically significant difference in visual acuity improvement but a small improvement in odds of 20/20 vision with NSAID. Abstract : Purpose: To compare visual outcomes in patients without a history of macular edema after phacoemulsification using combination topical nonsteroidal anti-inflammatory drug plus prednisolone with prednisolone alone. Setting: Kaiser Permanente Northern California, USA. Design: Retrospective cohort study. Methods: Information was obtained from the electronic health record. The first measure of corrected distance visual acuity (CDVA) recorded during the period 3 weeks to 1 year after phacoemulsification was obtained. Confounding factors and clustering of eyes within patients were adjusted using linear mixed effects regression models for the continuous outcome of CDVA improvement and general estimating equations for the dichotomous outcome of 20/20 or better vs 20/25 or worse. Results: The study included 62 700 health plan members of whom 26, 309 (42%) used topical prednisolone alone, whereas 36, 391 (58%) used combination treatment. The mean within-person change in CDVA from the preoperative measurement to the postoperative measurement was the same (−0.43 logMAR) for patients in the 2 groups. However, the group that received combination treatment was somewhat more likely to achieve CDVA of 20/20 or better (odds ratio 1.24 with 95% CI, 1.20-1.28). Conclusions: In this large study of cataract surgery patients, a small statistically significant association of combination treatment compared with prednisolone alone was observed.